Teaching and education in fracture and fatigue - Rossmanith, H.-P. (Hans-Peter) (ISTLI special publication, 1996)
This proceedings contains the best contributions to the series of seminars held in Vienna (1992), Miskolc, Hungary (1993 and 1994) and Vienna (1995) and provides a valuable resource for those concerned with the teaching of fracture and fatigue. It presents a wide range of approaches relevant to course and curriculum development. It is aimed particularly at those concerned with graduate and post-graduate education.